Effect of carotid ligation on cerebral blood flow in baboons: 1. Response to altered arterial PCO2. Issue 5 (October 1973) - Sengupta, D.; Harper, Murray; Jennett, B.
Abstract : Measurements of cerebral blood flow (CBF) were made in anaesthetized baboons before and after ipsilateral carotid artery ligation and also after bilateral carotid ligation. Results showed that at normocapnia (PaCO2 38-39 mmHg) there was little change in cerebral blood flow on ipsilateral carotid ligation, but when both carotid arteries were tied the blood flow to the brain fell significantly. At hypercapnia (PaCO2 58-60 mmHg) the CBF/CO2 gradient fell significantly on ipsilateral carotid ligation; on bilateral carotid ligation there was only minimal rise in cerebral blood flow in response to the rise in PaCO2 . At hypocapnia (PaCO2 20-21 mmHg) the gradients of fall in the CBF were similar before and after ipsilateral carotid ligation; after bilateral carotid ligation there was minimal change in the CBF in response to the fall in the PaCO2 . It is suggested that, although cerebral blood flow may be normal after ipsilateral carotid ligation, the circulatory reserve of the brain is not sufficient to meet physiological challenges. This may be the reason for the development of delayed neurological complications after carotid artery ligation.